Outcomes in COVID-19 patients undergoing laparoscopic cholecystectomy/appendectomy in the pre-vaccine era - Steven K.M. Vuu; Huazhi Liu; Darwin N. Ang (Surgery in Practice and Science, 2023)
Background: We hypothesized that COVID-19 positive patients requiring laparoscopic cholecystectomy (lap chole) or appendectomy (lap appy) would have increased inpatient mortality rates compared to all COVID-19 patients. Methods: Retrospective cohort analysis including COVID-19 patients from 1/1/20 to 9/30/20. 82,574 cases identified. Patients excluded if <18 years old or underwent surgery other than lap chole or lap appy. Control groups were patients without surgery (N = 82,145). Exposure groups underwent lap chole (N = 323) or lap appy (N = 106). Primary outcome was inpatient mortality. Secondary outcomes included hospital length of stay (LOS) and complications such as bacterial pneumonia, deep venous thrombosis (DVT), pulmonary embolism (PE), urinary tract infection (UTI), acute myocardial infarction (MI), acute respiratory distress syndrome (ARDS), and respiratory failure (RF). Results: Overall inpatient mortality rate was 32.8% in COVID-19 patients undergoing lap chole (p-value <0.0001), 2.8 % lap appy (p-value 0.93), and 1.2 % in control group. ARDS complication rate was 11.2 % in lap chole (p-value <0.0001), 1.9 % lap appy (p-value 0.71), and 0.2 % in control. Conclusion: COVID-19 patients during the initial wave of the pandemic who underwent lap chole during hospital admission had significantly higher risk of mortality and ARDS while lap appy did not.